2011
DOI: 10.1007/s10661-011-2151-2
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-FLD determination of 4-nonylphenol and 4-tert-octylphenol in surface water samples

Abstract: A simple, sensitive and reliable HPLC-FLD method for the routine determination of 4-nonylphenol, 4-NP and 4-tert-octylphenol, 4-t-OP content in water samples was developed. The method consists in a liquid-liquid extraction of the target analytes with dichloromethane at pH  3.0-3.5 followed by the HPLC-FLD analysis of the organic extract using a Zorbax Eclipse XDB C8 column, isocratic elution with a mixed solvent acetonitrile/water 65:35, at a flow rate of 1.0 mL/min and applying a column temperature of 40°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
0
5
1
3
Order By: Relevance
“…Table 3 lists the performance of the presented method for the determination of NP and 4-tOP from aqueous samples compared with the corresponding reported performance of other reported methods [26,[30][31][32][33]. It can be clearly observed that the proposed method has better performance in terms of the quantity of sample and solvent used.…”
Section: Comparison With Other Methodsmentioning
confidence: 98%
“…Table 3 lists the performance of the presented method for the determination of NP and 4-tOP from aqueous samples compared with the corresponding reported performance of other reported methods [26,[30][31][32][33]. It can be clearly observed that the proposed method has better performance in terms of the quantity of sample and solvent used.…”
Section: Comparison With Other Methodsmentioning
confidence: 98%
“…The most commonly used solid phase was the nonpolar character (C18) (Liu et al 2004, Cai et al 2003, Ciofi et al 2014, Souza, 2011Fabregat-Cabello et al 2013, Petrie et al 2013, Martinez and Peñuela 2013, de Sousa Leite et al 2010, Gatidou et al 2007, Petrovic et al 2003, Jeannot et al 2002, Díaz et al 2002, Fiedler et al 2007, Su et al 2012), but also observed in works which deployed solid phase of polymeric nature, with retention capability of polar and nonpolar analytes together (Azevedo et al 2001, Jeannot et al 2002, Terzopoulou et al 2014, Kuch and Ballschmiter 2001, Montagner and Jardim 2011, Sodré et al 2010b, Huerta et al 2015, Cruceru et al 2012. The major part of SPE uses cartridges containing 500 mg of solid phase and 6 ml volume capacity, but there are also works describing cartridges used with different stationary phase masses, such as 1000 mg, 60 mg and 200 mg. Other techniques used for extraction of nonylphenol in liquid samples are liquid-liquid extraction (Cruceru et al 2012, Oketola andFagbemigun 2013), the addition of ultrasound with SPE (Huerta et al 2015), use of DLLME (Sun et al 2013), and use of SPME (Díaz et al 2002, Hernández et al 2007.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Generally, BPA is used for manufacturing of raw materials of epoxy and polycarbonate resins [15,16] and also in the manufacturing of medical device and dental materials [17]. OP belongs to alkylphenol ethoxylates group and is widely used as nonionic surfactants in large variety of industrial and commercial applications [18].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%